2016
DOI: 10.1111/jnc.13717
|View full text |Cite
|
Sign up to set email alerts
|

Loss of divalent metal transporter 1 function promotes brain copper accumulation and increases impulsivity

Abstract: The divalent metal transporter 1 (DMT1) is a major iron transporter required for iron absorption and erythropoiesis. Loss of DMT1 function results in microcytic anemia. While iron plays an important role in neural function, the behavioral consequences of DMT1 deficiency are largely unexplored. The goal of this study was to define the neurobehavioral and neurochemical phenotypes of homozygous Belgrade (b/b) rats that carry DMT1 mutation and explore potential mechanisms of these phenotypes. The b/b rats (11–12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 104 publications
(187 reference statements)
1
20
0
Order By: Relevance
“…Functional studies using the duodenum from b/b rats revealed a ~70% reduction in Mn transport activity 45, 46 . Consistently, basal Mn levels are lower in the liver and blood of b/b rats compared with control rats 45, 47 . However, Shawki et al recently reported that specific-knockout of intestinal DMT1 does not affect the absorption or tissue distribution (including spleen, heart, kidney and liver) of Mn in mice 48 .…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Functional studies using the duodenum from b/b rats revealed a ~70% reduction in Mn transport activity 45, 46 . Consistently, basal Mn levels are lower in the liver and blood of b/b rats compared with control rats 45, 47 . However, Shawki et al recently reported that specific-knockout of intestinal DMT1 does not affect the absorption or tissue distribution (including spleen, heart, kidney and liver) of Mn in mice 48 .…”
Section: Introductionmentioning
confidence: 53%
“…However, the contribution of DMT1 to Mn distribution appears to be limited to the uptake process, and steady-state levels of Mn in the tissue could be more dependent on the export process. For example, b/b rats has lower or unchanged basal Mn levels in the liver compared with control rats 45, 47 , whereas the distribution of intravenously injected 54 Mn into the liver is greater in b/b rats 45 . Since the liver transfers Mn into the bile for excretion 92 , it is possible that Mn excretion is enhanced in b/b rats.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…DMT1 can be validated by using DMT1 mutant rats expressing nonfunctional DMT1. [109][110][111][112]144,145 3. The availability of HFE-deficient mice, a genetic model of iron overload hemochromatosis in humans, 113,114,[146][147][148] will allow investigators to explore the therapeutic efficacy of DMT1 siRNA against iron overload.…”
Section: The Model Of Oral Gene Silencing Specific Tomentioning
confidence: 99%
“…A few of investigations reported both sub‐acute and sub‐chronic toxic effect of metal mixture on hypothalamus, anterior pituitary as well as cerebrum using animal models (Bo & Yanli, ; Han, Chang, & Kim, ; Menon, Chang, & Kim, ). Also, from our laboratory, metabolic alterations involving antagonistic and competitive interactions were speculated as the major mechanism by which mixed‐metals elicit their toxic manifestations in brain tissues (Akintunde & Oboh, ).…”
Section: Introductionmentioning
confidence: 99%